2013
DOI: 10.1155/2013/374064
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Granger Causality with the Hilbert-Huang Transform

Abstract: Current measures of causality and temporal precedence have limited frequency and time resolution and therefore may not be viable in the detection of short periods of causality in specific frequencies. In addition, the presence of nonstationarities hinders the causality estimation of current techniques as they are based on Fourier transforms or autoregressive model estimation. In this work we present a combination of techniques to measure causality and temporal precedence between stationary and nonstationary ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This conditional variable can take the form of a scalar or a vector time series (Geweke, ). According to Rodrigues and Andrade (), such conditional time variable contains the remaining channels that must be included in the VAR model to discern between direct or mediated influences between the two variables being observed. In this paper, we estimate the conditional time Granger causality test through the use of a multivariate VAR (M‐VAR) model of the p th order, specified as: Δ S t = i = 1 p γ i ( Δ E ) t i + i = 1 p δ i ( Δ S ) t i + i = 1 p φ i ( I ) t i + u | t where I is the conditional time variable.…”
Section: Resultsmentioning
confidence: 99%
“…This conditional variable can take the form of a scalar or a vector time series (Geweke, ). According to Rodrigues and Andrade (), such conditional time variable contains the remaining channels that must be included in the VAR model to discern between direct or mediated influences between the two variables being observed. In this paper, we estimate the conditional time Granger causality test through the use of a multivariate VAR (M‐VAR) model of the p th order, specified as: Δ S t = i = 1 p γ i ( Δ E ) t i + i = 1 p δ i ( Δ S ) t i + i = 1 p φ i ( I ) t i + u | t where I is the conditional time variable.…”
Section: Resultsmentioning
confidence: 99%
“…An instantaneous measure of causality which is relying on the information versions of directed transfer entropy and partial directed coherence estimated after decomposing the coherencies and partial coherencies is presented in [ 166 ]. Instantaneous Granger causality measures based on the the Hilbert-Huang transform are introduced in [ 167 ].…”
Section: Directional Connectivity Measuresmentioning
confidence: 99%
“…An MHHS model for characterizing imagined motor actions has shown that asymmetry, a measure which characterizes the lateralization of amplitude information between two components, is more accurately extracted compared with approaches based on the Fourier spectrum [21]. More recent contributions include modelling coherence within the HHS domain via MEMD [23], and ways of estimating directionality with coherence and Granger causality within the IMF and HHS domains via EEMD [24]. [8], while Li et al [18] calculated spectral entropy using the MHHS and found that it was better suited to tracking responses to anaesthesia in EEG than other spectral entropy measures.…”
Section: Introductionmentioning
confidence: 99%